Polystyrene microplastics exposure in freshwater fish, Labeo rohita: evaluation of physiology and histopathology - Eram Rashid; Syed Makhdoom Hussain; Shafaqat Ali; Dariusz Kucharczyk; Joanna Nowosad; Khalid A. Al-Ghanim (Scientific Reports)
Abstract The goal of this investigation was to assess the adverse impacts of polystyrene microplastics (PS-MPs) on Labeo rohita with a comprehensive assessment of growth performance, hematological changes, and histopathological effects. Six test diets were established with different MPs levels using canola meal as the basal diet: control 0.0%, 0.5%, 1%, 1.5%, 2%, and 2.5% MPs. For 90 days, 315 fish (15 fish per tank with three replicates) were fed experimental diets at a rate of 5% of their live, twice a day. L. rohita fingerlings treated with 2.5% MPs leading to a notable decline in growth and feed consumption (P < 0.05). As PS-MPs increased, carcass, mineral and digestibility content declined. Additionally, a histology of the gut revealed significant abnormalities in intestine, including villi structure disruption and increased mucus cell proliferation, at a 2.5% PS-MPs concentration. Hematological indices such as RBCs, Hb, PLT, MCHC, and PCV decreased significantly when exposed to MPs, whereas WBCs, MCH, and MCV dramatically increased. Conclusively, this study demonstrated that the PS-MPs exert detrimental effects on growth performance, and induce histopathological and hematological changes in L. rohita.